CORRELATION OF SEVERITY OF ST SEGMENT ELEVATION IN ACUTE INFERIOR WALL MYOCARDIAL INFARCTION WITH THE PROXIMITY OF RIGHT CORONARY ARTERY DISEASE - Naqvi, Moazzam Ali; Ali, Muzaffar; Hakeem, Fuad; Masood, Arslan; Akram, Zubair (Journal of Ayub Medical College Abbottabad, 2008)
Background: A number of researchers have used different electrocardiographical criteria to predict the culprit vessel in acute inferior wall myocardial infarction (MI) cases. Therefore, the determination of infarct related artery in AMI is extremely important with regard to prediction of potential complications, furthermore, predicting the probable site of occlusion within RCA is worthwhile because proximal occlusions are likely to cause greater myocardial damage and an early invasive strategy may be planned in such cases. Our study aimed at evaluating the ECG criteria to predict the proximity of lesion in the right coronary artery (RCA) in acute inferior wall MI cases. The Objectives were to predict the presence of a proximal lesion in right coronary artery by severity of ST segment elevation in inferior ECG leads. This cross-sectional study carried out at the department of cardiology and cardiac catheterization at Jinnah Hospital, Lahore from April 2008 to September 2008. Methods: A total of 60 patients who suffered from inferior wall MI were included in the study who underwent coronary angiography in the first week. The ECGs of these patients were then compared with the angiographic findings to correlate the proximity of culprit lesion in RCA with the degree of ST segment elevation in inferior limb leads. Results: Out of 60 patients, 29 (48.4%) had the culprit lesion in proximal, 23 (38.5%) in mid and 8 (13.4%) in distal RCA. Patients with proximal RCA disease showed a mean ST segment elevation of 12.55±1.38 mm, with mid RCA disease 8.39±0.89 mm and with distal RCA disease 6.0±0.54 mm. Conclusion: This study demonstrated that the severity of ST segment elevation was correlated with proximity of RCA lesion Keywords: Right coronary artery, ST elevation MI, Acute Myocardial infarction